Effects of added trunk load and corresponding trunk position adaptations on lower extremity biomechanics during drop-landings - Kulas, A.; Zalewski, P.; Hortobagyi, T.; DeVita, P. (Journal of Biomechanics, 2008)
Although both trunk mass and trunk position have the potential to affect lower extremity biomechanics during landing, these effects are not well understood. Our overall hypothesis stated that both trunk mass and trunk position affect lower extremity biomechanics in landing. Thus, our purpose was to determine the effects of an added trunk load and kinematic trunk adaptation groups on lower extremity joint kinematics, kinetics, and energetics during drop-landings. Twenty-one recreationally active subjects were instrumented for biomechanical analysis. Subjects performed two sets of eight double-limb landings with and without 10% body weight added to the trunk. On lower extremity dependent variables, 2(condition: no load, trunk load)×2(group: trunk extensors vs. trunk flexors) ANOVAs were performed. Condition by group interactions at the hip showed differing responses to the added trunk load between groups where the trunk extensor group decreased hip extensor efforts (11-18%) while the trunk flexor group increased hip extensor efforts (14-19%). The trunk load increased biomechanical demands at the knee and ankle regardless of trunk adaptation group. However, the percent increases in angular impulses and energy absorption in the trunk extensor group were 14-28% while increases in the trunk flexor group were 4-9%. Given the 10% body weight added to the trunk, the 14-28% increases at the knee and ankle in the trunk extensor group were likely due to the reduced hip extensor efforts during landing. Overall these findings support our overall hypothesis that both trunk mass and trunk position affect lower extremity biomechanics during vertically oriented landing tasks.